1998
DOI: 10.3354/meps169113
|View full text |Cite
|
Sign up to set email alerts
|

Xanthophyll cycling in Phaeocystis antarctica:changes in cellular fluorescence

Abstract: The xanthophyll cycle has been implicated as a possible photoprotective mechanism in higher plants and algae by dissipating excess excitation energy via non-photochemical q.uenching. To examine whether colonial Phaeocystis antarctica Karsten displays xanthophyll cycling, nutrient-replete c u l t u r~s were initially grown under limiting (40 pm01 quanta m -2 s~' ) and saturating (280 pm01 quanta m-2 S -' ) irradiances for photosynthesis and their responses to irradiance transitions were examined for 1 h under 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 16 publications
3
43
0
Order By: Relevance
“…Some species acclimate by changing the size of the light harvesting antenna of the individual reaction centre, while others increase the total number of reaction centres, keeping antenna size constant (Falkowski and LaRoche, 1991;Moore et al, 2006). As with temperate diatoms (Ruban et al, 2004;Dimier et al, 2007;Lavaud et al, 2007), SO-and sea ice diatoms are highly plastic to fluctuations in light with a strong dependence on rapid and reversible xanthophyll cycling (Moisan et al, 1998;Moisan and Mitchell, 1999;Kropuenske et al, 2009;Petrou et al, 2011a,c), however, not all species utilise the same strategies, nor have the same level of physiological plasticity (Kropuenske et al, 2009;Mills et al, 2010;Petrou et al, 2011a). This physiological variability results in a wide range of light utilisation efficiency and photoprotective capacities from one phytoplankton species to another, making it important to investigate species-specific photosynthetic activity to understand what drives community composition and ultimately primary productivity.…”
Section: Lightmentioning
confidence: 99%
See 1 more Smart Citation
“…Some species acclimate by changing the size of the light harvesting antenna of the individual reaction centre, while others increase the total number of reaction centres, keeping antenna size constant (Falkowski and LaRoche, 1991;Moore et al, 2006). As with temperate diatoms (Ruban et al, 2004;Dimier et al, 2007;Lavaud et al, 2007), SO-and sea ice diatoms are highly plastic to fluctuations in light with a strong dependence on rapid and reversible xanthophyll cycling (Moisan et al, 1998;Moisan and Mitchell, 1999;Kropuenske et al, 2009;Petrou et al, 2011a,c), however, not all species utilise the same strategies, nor have the same level of physiological plasticity (Kropuenske et al, 2009;Mills et al, 2010;Petrou et al, 2011a). This physiological variability results in a wide range of light utilisation efficiency and photoprotective capacities from one phytoplankton species to another, making it important to investigate species-specific photosynthetic activity to understand what drives community composition and ultimately primary productivity.…”
Section: Lightmentioning
confidence: 99%
“…This plasticity is not common to all SO diatoms, instead other species exposed to the same stressors, have shown to be less plastic to changes in light, exhibiting limited NPQ capacity and no dynamic control over excitation pressure (Petrou et al, 2011a, highlighting how photoacclimation strategy may be an important determinant of the success of F. cylindrus in polar marine environments (Kang and Fryxell, 1992;Lizotte, 2001;Kopczynska et al, 2007). As with F. cylindrus, the photoacclimation strategy of the prymnesiophyte Phaeocystis antarctica provides us with some insight into the success of this species, including its fast photoacclimation capabilities (Moisan et al, 1998;Kropuenske et al, 2009Kropuenske et al, , 2010 and high investment into carotenoid synthesis under Fe limitation (van Leeuwe and Stefels, 2007). While it appears that these two species utilise similar strategies, studies directly comparing P. antarctica with F. cylindrus found that the former was able to acclimate to changes in irradiance much faster than the diatom, but was much slower to induce NPQ, resulting in more photoinhibitory quenching (Kropuenske et al, 2009;Mills et al, 2010) and a high dependence on photosynthetic protein repair processes (Kropuenske et al, 2009.…”
Section: Lightmentioning
confidence: 99%
“…Krause & Weis 1991), giving an apparent decrease in biomass. In laboratory low-to-high light studies, nonphotochemical quenching resulted in an initial average rate of change in fluorescence of 4% min -1 (SE = 0.8, n = 13) (from graphs and tables in: Kiefer 1973, Sakshaug et al 1987, Cullen & Lewis 1988, Demers et al 1991, Olaizola et al 1994, Moisan et al 1998. A sudden change from high light to low light is predicted to give the opposite effect: an apparent increase in biomass with a time scale of minutes.…”
Section: Predictionmentioning
confidence: 99%
“…The average rate during summer, although larger, was not significantly different from the laboratory studies (7% min -1 , SE = 1.5; p = 0.15). It may be significant that laboratory studies of non-photochemical quenching generally show the increasing fluorescence response time to be somewhat longer than the decreasing fluorescence response time (Kiefer 1973, Sakshaug et al 1987, Demers et al 1991, Moisan et al 1998, whereas the changes in fluorescence measured in the field were typically symmetric (same rate of increase and decrease during a wave; Figs. 3 & 8).…”
Section: Testmentioning
confidence: 99%
“…The function of the 4-keto derivatives is unknown. The universally distributed carotenoid pair diadinoxanthin and diatoxanthin, present in all haptophytes examined, have a well-established photoprotective function via the light-regulated epoxide cycle (Stransky & Hager 1970, Siefermann-Harms 1985, Demmig-Adams & Adams 1993, Moisan et al 1998, Lohr & Wilhelm 1999. Further study is needed to understand the function and biosynthetic regulation of all these important marine pigments, and their consequent reliability as chemotaxonomic indicators in field oceanography.…”
Section: Possible Pigment Functionsmentioning
confidence: 99%